Three-dimensional Ni-Al LDHs nanoflower composite material and preparation method and application thereof

By introducing g-C3N4 dopant, Ni-Al LDHs sheet structure distorted, a composite material with nano-scale three-dimensional flower-like structure was prepared, which solved the problem of performance degradation of Ni-Al LDHs gas-sensitive materials in high humidity environments. Improves gas sensitivity and selectivity and shortens response time.

CN119503899APending Publication Date: 2025-02-25HEILONGJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411644771.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

As a gas-sensitive material, Ni-Al LDHs have problems such as small specific surface area, high operating temperature, low sensitivity, long response/recovery time and high cost, especially in high humidity environments, which are prone to performance degradation or failure.

Method used

By introducing g-C3N4 as a dopant, the structural distortion of the Ni-Al LDHs sheet structure was produced, and a composite material with a microscopic morphology of nanoscale three-dimensional flower-like structure was prepared. This structure is not only conducive to the permeation and diffusion of gas molecules, but also forms a humidity shielding effect and improves moisture resistance.

Benefits of technology

It improves the gas sensitivity of the composite material and selectivity to NO2 molecules, shortens the response time, and maintains the structural and performance stability of the material under high humidity environment, ensuring the accuracy and reliability of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to a three-dimensional Ni-Al LDHs nanoflower composite material as well as a preparation method and application thereof, and belongs to the technical field of gas sensitive materials. In order to solve the problems of high working temperature, low sensitivity, long response / recovery time and high cost of Ni-Al LDHs as a gas sensitive material, the invention provides a three-dimensional Ni-Al LDHs nanoflower composite material which is prepared by doping g-C3N4 and has a microstructure consisting of a plurality of lamellar structures. According to the invention, g-C3N4 is used as a dopant to cause structural distortion, and abundant pores and channels among a plurality of obtained lamellar structures form a humidity shielding effect, so that the composite material can maintain sensitivity and selectivity to target gas in a high-humidity environment. The lamellar structure is not easy to collapse or deform in a humidity environment, the stability of the structure and the performance of the lamellar structure is maintained, the performance of the gas sensitive sensor in the humidity environment can be remarkably improved, and the lamellar structure has important application prospects in the field of NO2 gas detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas-sensitive materials, and in particular relates to a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method and application thereof. Background Art

[0002] Semiconductor gas-sensitive materials are a new type of solid material with good gas-sensitive properties. Their advantages are small size, light weight, low energy consumption, stability and reliability. In recent years, semiconductor gas-sensitive materials have been widely used due to their ability to efficiently sense, sense and respond to changes in environmental gas composition, including air pollution detection, indoor air pollution control, medical diagnosis and environmental monitoring, etc.

[0003] Ni-Al LDHs (nickel aluminum layered double hydroxide) is a layered double metal hydroxide with a unique layered structure and chemical properties. When Ni-Al LDHs is used as a gas-sensitive material, its layered structure and surface chemical properties make it highly sensitive to gas molecules in the environment. The adsorption and desorption process of these gas molecules on the surface of Ni-Al LDHs will cause significant changes in the electrical properties of the material, such as changes in resistivity, so that the type and concentration of the gas can be detected by measuring the changes in these electrical properties. However, there may be stacking between the Ni-Al LDHs layers, which affects the penetration of gas molecules and the response speed of the sensor. Moreover, the two-dimensional structure Ni-Al LDHs gas-sensitive material is easily affected by humidity, causing the drift of the baseline resistance, the reduction of gas response and the fluctuation of sensor performance, resulting in false alarms or missed alarms in practical applications.

[0004] The invention patent with application publication number CN110665527A discloses a sea urchin-shaped g-C3N4 / NiAl-LDH semiconductor heterojunction composed of g-C3N4 and NiAl LDH nanosheets, wherein g-C3N4 is the core of a hollow sphere, and the thorn-shaped NiAl-LDH nanosheets are in-situ grown on the surface of the g-C3N4 hollow sphere to form a 3D sea urchin hierarchical structure. Although this three-dimensional morphology structure has a larger specific surface area and surface active sites, it is conducive to the penetration of gas molecules and the response of the sensor. However, its internal cavity will become a "trap" for water molecules in a humid environment. After water molecules enter the cavity, it is difficult to quickly discharge, resulting in an increase in the humidity inside the material, which is prone to performance degradation or failure. There are different interface effects inside and outside the hollow sphere under a humid environment, which can easily lead to the destruction of the material structure.

[0005] Therefore, how to further improve the moisture resistance of Ni-Al LDHs as gas-sensitive materials while maintaining the sensitivity, selectivity and material structure stability to the target gas remains an urgent problem to be solved in this field. Summary of the invention

[0006] In order to solve the problems of small specific surface area, high operating temperature, low sensitivity, long response / recovery time and high cost of Ni-Al LDHs as gas-sensitive materials, the present invention provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method and application thereof.

[0007] The technical solution of the present invention:

[0008] A preparation method of a three-dimensional Ni-Al LDHs nanoflower composite material comprises the following steps: firstly calcining urea twice to obtain a two-dimensional g-C3N4 precursor, then placing the two-dimensional g-C3N4 precursor, nickel nitrate hexahydrate, aluminum nitrate nonahydrate, ammonium fluoride and urea in deionized water, stirring to obtain a mixed solution I, placing the mixed solution I in an autoclave for heating treatment, cooling to obtain a mixed solution II, filtering the mixed solution II to collect a precipitate, washing and drying to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0009] Furthermore, the heating rate of the first calcination of urea is 2.4°C / min, the first calcination temperature is 500-550°C, and the calcination time is 2-4h; the heating rate of the second calcination of urea is 5°C / min, the second calcination temperature is 20-50°C lower than the first calcination temperature, and the calcination time is 2h.

[0010] Furthermore, the mass to volume ratio of the two-dimensional g-C3N4 precursor, nickel nitrate hexahydrate, aluminum nitrate nonahydrate, ammonium fluoride, urea and deionized water is 0.12-0.15g: 0.1g: 0.05g: 0.04-0.06g: 0.1g: 70-80mL; and the stirring time is 30-60min.

[0011] Furthermore, the mixed solution I is heated at 100-150° C. for 18-24 hours.

[0012] Furthermore, the washing is to wash the precipitate obtained by filtration with deionized water and anhydrous ethanol in sequence, and the drying is to dry at 60 to 90° C. for 12 to 24 hours.

[0013] A three-dimensional Ni-Al LDHs nanoflower composite material prepared by a preparation method of a three-dimensional Ni-Al LDHs nanoflower composite material provided by the present invention, wherein the composite material is a g-C3N4 doped Ni-Al LDHs composite material, and the microscopic morphology of the composite material is a nanoscale three-dimensional flower-like structure composed of a plurality of lamellar structures, the diameter of the overall three-dimensional flower-like structure is 2 to 3 μm, and the specific surface area is 140 to 150 m 2 / g.

[0014] The invention discloses an application of a three-dimensional Ni-Al LDHs nanoflower composite material prepared by the invention in NO2 gas detection.

[0015] Furthermore, the application is to prepare a gas sensor using a three-dimensional Ni-Al LDHs nanoflower composite material.

[0016] Furthermore, the preparation method of the gas sensor is to ultrasonically disperse the Ni-Al LDHs nanoflower composite material prepared by the present invention in 1 to 10 times the volume of an ethanol solution to obtain a uniformly dispersed suspension, and then coat the suspension on an Au interdigital electrode cleaned with ethanol, and place it at 50 to 90° C. and dry it for 2 to 5 hours to obtain a gas sensor.

[0017] Furthermore, the application is to place the gas sensor prepared from the three-dimensional Ni-Al LDHs nanoflower composite material of the present invention under the conditions of 15-35° C. and 20-80% humidity to detect the NO2 gas concentration in the gas to be tested.

[0018] Beneficial effects of the present invention:

[0019] The present invention uses g-C3N4 as a dopant to cause structural distortion of Ni-Al LDHs sheets, and prepares a composite material with a nanoscale three-dimensional flower-like structure in microscopic morphology. A plurality of lamella structures in the nanoflower structure form abundant pores and channels, which are not only conducive to the penetration and diffusion of gas molecules, but also can form a certain humidity shielding effect, making it difficult for water molecules to directly contact the sensitive layer of the composite material, thereby improving the moisture resistance of the composite material, and enabling it to maintain sensitivity and selectivity to the target gas in a high humidity environment. The plurality of lamella structures in the three-dimensional nanoflower structure are tightly and stably connected, so that the composite material is not prone to structural collapse or deformation in a humidity environment, thereby maintaining the stability of its structure and performance. This stability helps to ensure the accuracy and reliability of the sensor during long-term use in a humidity environment.

[0020] The present invention regulates the surface properties of the three-dimensional Ni-Al LDHs nanoflower composite material by causing structural distortion through g-C3N4 doping during the preparation process, thereby increasing the specific surface area, providing more active sites, and increasing the contact probability between the composite material and NO2 molecules to optimize the adsorption process, thereby reducing the influence of humidity on target gas detection to a certain extent, improving the gas sensitivity of the composite material and the selectivity for NO2 molecules, and further shortening the response time.

[0021] The three-dimensional Ni-Al LDHs nanoflower composite material provided by the present invention is used to prepare a gas sensor, and it is used to detect the NO2 gas concentration in the gas to be tested at room temperature. The sensitivity to the NO2 gas with a concentration of 100ppm is 51.73, and the response time is 1.07 seconds. When the NO2 concentration decreases, the response value also decreases, and the minimum detection limit is 0.01ppm, the corresponding response value is 1.18, and the response time is 11.73 seconds. After multiple NO2 adsorption and desorption tests, the repeatability of the three-dimensional Ni-Al LDHs nanoflower composite material is still excellent, indicating that the composite material has high sensitivity and good repeatability, and can reduce the cost of gas sensors.

[0022] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material provided by the present invention has the characteristics of simple process, low cost, and environmentally friendly and non-toxic production process. The prepared three-dimensional Ni-Al LDHs nanoflower composite material can significantly improve the performance of gas sensors and has important application prospects in the field of NO2 gas detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The scanning electron microscope images of the three-dimensional Ni-Al LDHs nanoflower composite material, the two-dimensional Ni-Al LDHs and the two-dimensional g-C3N4 precursor, in which a is the three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 1, b is the two-dimensional Ni-Al LDHs, and c is the two-dimensional g-C3N4 precursor;

[0024] Figure 2 This is the pore size distribution diagram of the three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 1;

[0025] Figure 3 It is a N2 adsorption-desorption curve diagram of the three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 1;

[0026] Figure 4 The X-ray diffraction pattern of the three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 1;

[0027] Figure 5 The sensitivity curve of the gas sensor prepared in Example 7 for detecting NO2 gas;

[0028] Figure 6 This is a gas selectivity test diagram of the gas sensor prepared in Example 7 at room temperature;

[0029] Figure 7 The sensitivity curve of the gas sensor prepared in Example 8 for detecting NO2 gas;

[0030] Figure 8This is a graph showing the repeatability test results of the gas sensor prepared in Example 8 for 100 ppm NO2 at room temperature.

[0031] Fig. 9 This is the dynamic response curve of the gas sensor prepared in Example 8 to 100 ppm NO2 at different relative humidity (RH) at room temperature. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0033] Example 1

[0034] This embodiment provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method thereof.

[0035] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material in this embodiment comprises the following steps:

[0036] Step 1: Preparation of two-dimensional g-C3N4 precursor:

[0037] 10 g of urea was put into a crucible and calcined in a muffle furnace for the first time. The calcination temperature was raised to 550°C at a heating rate of 2.4°C / min, and the calcination was carried out for 4 hours. After natural cooling, the calcination temperature was raised to 500°C at a heating rate of 5°C / min, and the calcination was carried out for the second time. The product was collected to obtain a two-dimensional g-C3N4 precursor;

[0038] Step 2: Preparation of three-dimensional Ni-Al LDHs nanoflower composite materials:

[0039] 0.15 g of the g-C3N4 precursor obtained in step 1 is placed in 70 ml of deionized water with 0.1 g of nickel nitrate hexahydrate, 0.05 g of aluminum nitrate nonahydrate, 0.04 g of ammonium fluoride and 0.1 g of urea, and stirred for 45 min to obtain a mixed solution I. The mixed solution I is placed in an autoclave and heated at a constant temperature of 130°C for 20 h. After cooling, a mixed solution II is obtained. The mixed solution II is filtered and the precipitate is washed with 1000 ml of deionized water and 500 ml of anhydrous ethanol in turn, and the precipitate is collected; the washed precipitate is placed in a drying oven and dried at 65°C for 20 h to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0040] Figure 1 Figure 1 is a scanning electron microscope image of a three-dimensional Ni-Al LDHs nanoflower composite material, a two-dimensional Ni-Al LDHs and a two-dimensional g-C3N4 precursor, wherein a is a three-dimensional Ni-Al LDHs nanoflower composite material prepared in this embodiment, b is a two-dimensional Ni-Al LDHs, and c is a two-dimensional g-C3N4 precursor; by comparison, it can be clearly seen that the three-dimensional flower-like structure has a richer lamellar structure, and abundant pores and channels are formed between the lamellar structures, such as Figure 2 The average pore size of the pores shown is 2.34 nm.

[0041] Figure 3 This is a graph of the N2 adsorption-desorption curve of the three-dimensional Ni-Al LDHs nanoflower composite material prepared in this embodiment; the curve in the figure can illustrate that there are a large number of micropores in the three-dimensional Ni-Al LDHs nanoflower composite material. The abundant pores and channels are not only conducive to the penetration and diffusion of gas molecules, but also can form a certain humidity shielding effect, making it difficult for water molecules to directly contact the sensitive layer of the composite material, improving the moisture resistance of the composite material, so that it can maintain sensitivity and selectivity to the target gas in a high humidity environment. The diameter of the overall three-dimensional flower-like structure is 2 to 3 μm, and the several layer structures in the three-dimensional nanoflower structure are tightly connected and stable, so that the composite material is not prone to structural collapse or deformation in a humid environment, thereby maintaining the stability of its structure and performance. This stability helps to ensure the accuracy and reliability of the sensor during long-term use in a humid environment.

[0042] Figure 4 The X-ray diffraction diagram of the three-dimensional Ni-Al LDHs nanoflower composite material prepared in this embodiment; it can be seen from the figure that the diffraction peaks of the compound, that is, the 2θ angle values ​​of 11.4°, 23.1°, 34.9°, 39.3°, 46.8°, 60.1°, and 62.1° respectively coincide with the (003), (006), (012), (015), (018), (110), and (113) crystal planes of the standard card of Ni-Al LDHs, and the 2θ angle value of 27.4° coincides with the (002) crystal plane of the standard card of g-C3N4, thereby confirming that the present invention successfully synthesizes the g-C3N4 doped Ni-Al LDHs composite material. During the reaction process, g-C3N4 doping causes structural distortion, optimizes the surface properties of the three-dimensional Ni-AlLDHs nanoflower composite material, and increases the specific surface area to 140 to 150 m 2 / g, which produces more active sites, increases the contact probability between the composite material and NO2 molecules and optimizes the adsorption process, reduces the influence of humidity on target gas detection to a certain extent, improves the gas sensitivity of the composite material and its selectivity to NO2 molecules, and further shortens the response time.

[0043] Example 2

[0044] This embodiment provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method thereof.

[0045] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material in this embodiment comprises the following steps:

[0046] Step 1: Preparation of two-dimensional g-C3N4 precursor:

[0047] 10 g of urea was put into a crucible and calcined in a muffle furnace for the first time. The calcination temperature was increased to 550 ° C at a heating rate of 2.4 ° C / min, and the temperature was kept constant for 3 hours. After natural cooling, the second calcination was carried out. The calcination temperature was increased to 520 ° C at a heating rate of 5 ° C / min, and the temperature was kept constant for 2 hours. The product was collected to obtain a two-dimensional g-C3N4 precursor;

[0048] Step 2: Preparation of three-dimensional Ni-Al LDHs nanoflower composite materials:

[0049] 0.12 g of the g-C3N4 precursor obtained in step 1 is placed in 70 ml of deionized water with 0.1 g of nickel nitrate hexahydrate, 0.05 g of aluminum nitrate nonahydrate, 0.06 g of ammonium fluoride and 0.1 g of urea, and stirred for 45 min to obtain a mixed solution I. The mixed solution I is placed in an autoclave and heated at a constant temperature of 150°C for 18 h. After cooling, a mixed solution II is obtained. The mixed solution II is filtered and the precipitate is washed with 1000 ml of deionized water and 500 ml of anhydrous ethanol in turn, and the precipitate is collected; the washed precipitate is placed in a drying oven and dried at 65°C for 20 h to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0050] Example 3

[0051] This embodiment provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method thereof.

[0052] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material in this embodiment comprises the following steps:

[0053] Step 1: Preparation of two-dimensional g-C3N4 precursor:

[0054] 10 g of urea was put into a crucible and calcined in a muffle furnace for the first time. The calcination temperature was increased to 550°C at a heating rate of 2.4°C / min, and the calcination was carried out for 3 hours. After natural cooling, the calcination temperature was increased to 500°C at a heating rate of 5°C / min, and the calcination was carried out for the second time. The product was collected to obtain a two-dimensional g-C3N4 precursor;

[0055] Step 2: Preparation of three-dimensional Ni-Al LDHs nanoflower composite materials:

[0056] 0.12 g of the g-C3N4 precursor obtained in step 1 is placed in 70 ml of deionized water with 0.1 g of nickel nitrate hexahydrate, 0.05 g of aluminum nitrate nonahydrate, 0.05 g of ammonium fluoride and 0.1 g of urea, and stirred for 45 min to obtain a mixed solution I. The mixed solution I is placed in an autoclave and heated at a constant temperature of 120°C for 20 h. After cooling, a mixed solution II is obtained. The mixed solution II is filtered and the precipitate is washed with 1000 ml of deionized water and 500 ml of anhydrous ethanol in turn, and the precipitate is collected; the washed precipitate is placed in a drying oven and dried at 65°C for 18 h to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0057] Example 4

[0058] This embodiment provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method thereof.

[0059] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material in this embodiment comprises the following steps:

[0060] Step 1: Preparation of two-dimensional g-C3N4 precursor:

[0061] 10 g of urea was put into a crucible and calcined in a muffle furnace for the first time. The calcination temperature was increased to 550°C at a heating rate of 2.4°C / min, and the calcination was carried out for 3 hours. After natural cooling, the calcination temperature was increased to 500°C at a heating rate of 5°C / min, and the calcination was carried out for the second time. The product was collected to obtain a two-dimensional g-C3N4 precursor;

[0062] Step 2: Preparation of three-dimensional Ni-Al LDHs nanoflower composite materials:

[0063] 0.12 g of the g-C3N4 precursor obtained in step 1 is placed in 70 ml of deionized water with 0.1 g of nickel nitrate hexahydrate, 0.05 g of aluminum nitrate nonahydrate, 0.05 g of ammonium fluoride and 0.1 g of urea, and stirred for 45 min to obtain a mixed solution I. The mixed solution I is placed in an autoclave and heated at a constant temperature of 120°C for 20 h. After cooling, a mixed solution II is obtained. The mixed solution II is filtered and the precipitate is washed with 1000 ml of deionized water and 500 ml of anhydrous ethanol in turn, and the precipitate is collected; the washed precipitate is placed in a drying oven and dried at 65°C for 18 h to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0064] Example 5

[0065] This embodiment provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method thereof.

[0066] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material in this embodiment comprises the following steps:

[0067] Step 1: Preparation of two-dimensional g-C3N4 precursor:

[0068] 10 g of urea was put into a crucible and calcined in a muffle furnace for the first time. The calcination temperature was raised to 530 ° C at a heating rate of 2.4 ° C / min, and the temperature was kept constant for 4 hours. After natural cooling, the second calcination was carried out. The calcination temperature was raised to 510 ° C at a heating rate of 5 ° C / min, and the temperature was kept constant for 2 hours. The product was collected to obtain a two-dimensional g-C3N4 precursor;

[0069] Step 2: Preparation of three-dimensional Ni-Al LDHs nanoflower composite materials:

[0070] 0.15 g of the g-C3N4 precursor obtained in step 1 is placed in 70 ml of deionized water with 0.1 g of nickel nitrate hexahydrate, 0.05 g of aluminum nitrate nonahydrate, 0.05 g of ammonium fluoride and 0.1 g of urea, and stirred for 45 min to obtain a mixed solution I. The mixed solution I is placed in an autoclave and heated at a constant temperature of 120°C for 24 h. After cooling, a mixed solution II is obtained. The mixed solution II is filtered and the precipitate is washed with 1000 ml of deionized water and 500 ml of anhydrous ethanol in turn, and the precipitate is collected; the washed precipitate is placed in a drying oven and dried at 65°C for 18 h to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0071] Example 6

[0072] This embodiment provides a three-dimensional Ni-Al LDHs nanoflower composite material and a preparation method thereof.

[0073] The preparation method of the three-dimensional Ni-Al LDHs nanoflower composite material in this embodiment comprises the following steps:

[0074] Step 1: Preparation of two-dimensional g-C3N4 precursor:

[0075] 10 g of urea was put into a crucible and calcined in a muffle furnace for the first time. The calcination temperature was increased to 550°C at a heating rate of 2.4°C / min, and the calcination was carried out for 3 hours. After natural cooling, the calcination temperature was increased to 500°C at a heating rate of 5°C / min, and the calcination was carried out for the second time. The product was collected to obtain a two-dimensional g-C3N4 precursor;

[0076] Step 2: Preparation of three-dimensional Ni-Al LDHs nanoflower composite materials:

[0077] 0.12 g of the g-C3N4 precursor obtained in step 1 is placed in 70 ml of deionized water with 0.1 g of nickel nitrate hexahydrate, 0.05 g of aluminum nitrate nonahydrate, 0.05 g of ammonium fluoride and 0.1 g of urea, and stirred for 45 min to obtain a mixed solution I. The mixed solution I is placed in an autoclave and heated at a constant temperature of 150°C for 24 h. After cooling, a mixed solution II is obtained. The mixed solution II is filtered and the precipitate is washed with 1000 ml of deionized water and 500 ml of anhydrous ethanol in turn, and the precipitate is collected; the washed precipitate is placed in a drying oven and dried at 65°C for 18 h to obtain a three-dimensional Ni-Al LDHs nanoflower composite material.

[0078] Example 7

[0079] This embodiment provides a gas sensing element made of the three-dimensional MoS2 nanoflower composite material prepared in Example 1 as a gas sensing material.

[0080] The specific preparation method of the gas sensor in this embodiment is:

[0081] The three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 1 was ultrasonically dispersed in 5 times the volume of anhydrous ethanol solution to obtain a uniformly dispersed suspension, and then the suspension was spin-coated on the Au interdigital electrode cleaned with ethanol and dried at 60°C for 4 hours to obtain a gas sensor.

[0082] The prepared gas-sensitive element was subjected to gas-sensitive detection by a static gas distribution method, and the specific steps were as follows: first, the gas-sensitive element to be tested was installed in the gas chamber and connected to the information acquisition and analysis equipment; at a detection temperature of 25°C and a detection humidity of 25%, 100 ppm of NO2 was injected; when the gas-sensitive response was observed to be stable according to the information fed back by the data acquisition system, an air pump was used to evacuate the gas to desorb NO2, and the device to be tested returned to its initial state, completing a gas injection cycle; then, 100 ppm, 50 ppm, 30 ppm, 10 ppm, 5 ppm, 3 ppm, 1 ppm, 0.5 ppm, 0.3 ppm, 0.1 ppm, 0.05 ppm, 0.03 ppm and 0.01 ppm of NO2 gas injection cycles were performed in sequence; after completing the gas injection cycle, the following was obtained: Figure 5 The sensitivity curve of the gas sensor prepared in this embodiment for detecting NO2 gas is shown. The sensitivity to NO2 gas with a concentration of 100 ppm is 51.73, and the sensitivity to NO2 gas with a concentration as low as 0.01 ppm is 1.18. In addition, the material has a fast response speed and good adsorption reversibility.

[0083] Table 1 shows the sensitivity and response time of the gas sensor prepared in this embodiment under different NO2 gas concentrations, where the sensitivity S=Ra / Rg, Ra is the resistance of the sensor in air, and Rg is the resistance of the sensor in NO2 atmosphere. During the gas adsorption and desorption process, the time required for the resistance to change by 90% is the response time.

[0084] Table 1

[0085] <![CDATA[NO2 concentration]]> Sensitivity Response time 100ppm 51.73 1.07s 50ppm 44.97 1.60s 30ppm 34.93 1.60s 10ppm 26.40 2.13s 5ppm 20.85 2.67s 3ppm 14.56 3.20s 1ppm 2.09 3.73s 0.5ppm 1.78 5.33s 0.3ppm 1.70 6.93s 0.1ppm 1.64 9.60s 0.05ppm 1.49 10.13s 0.03ppm 1.41 10.67s 0.01ppm 1.18 11.73s

[0086] Figure 6 This is a gas selectivity test diagram of the gas sensor prepared in this embodiment at room temperature, wherein the test gases include: NO2, H2S, NH3, SO2 and N2O. Except for NO2 with an injection concentration of 100ppm, the injection concentrations of the other gases are 10000ppm. Figure 6 The results show that the gas sensor made of the three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 1 as a gas-sensitive material has excellent selectivity for NO2 at room temperature.

[0087] Example 8

[0088] This embodiment provides a gas sensing element made by using the three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 2 as a gas sensing material.

[0089] The specific preparation method of the gas sensor in this embodiment is:

[0090] The three-dimensional Ni-Al LDHs nanoflower composite material prepared in Example 2 was ultrasonically dispersed in 5 times the volume of anhydrous ethanol solution to obtain a uniformly dispersed suspension, and then the suspension was spin-coated on the Au interdigital electrode cleaned with ethanol and dried at 60°C for 4 hours to obtain a gas sensor.

[0091] The prepared gas-sensitive element was subjected to gas-sensitive detection by a static gas distribution method, and the specific steps were as follows: first, the gas-sensitive element to be tested was installed in the gas chamber and connected to the information acquisition and analysis equipment; at a detection temperature of 30°C and a detection humidity of 35%, 100 ppm of NO2 was injected; when the gas-sensitive response was observed to be stable according to the information fed back by the data acquisition system, an air pump was used to evacuate the gas to desorb NO2, and the device to be tested returned to its initial state, completing a gas injection cycle; then, 100 ppm, 50 ppm, 30 ppm, 10 ppm, 5 ppm, 3 ppm, 1 ppm, 0.5 ppm, 0.3 ppm, 0.1 ppm, 0.05 ppm, 0.03 ppm and 0.01 ppm of NO2 gas injection cycles were performed in sequence; after completing the gas injection cycle, the following was obtained: Figure 7The sensitivity curve of the gas sensor prepared in this embodiment for detecting NO2 gas shows that the sensitivity to the gas with NO2 concentration of 100ppm is 39.50, and the sensitivity to the gas with NO2 concentration as low as 0.1ppm is 1.02.

[0092] The gas sensing test performance under different humidity in this example is as follows:

[0093] First, exhaust other gases in the laboratory by passing air into the laboratory for at least three minutes. Next, inject steam into the laboratory and confirm that the test conditions have reached the required target humidity by observing the tank thermometer. Then inject 100ppm of nitrogen dioxide gas and record the resistance change caused by the introduction of nitrogen dioxide. When the resistance reaches the lowest point and tends to stabilize, turn on the vacuum pump to extract the remaining nitrogen dioxide gas in the laboratory so that the sensor resistance reaches the starting resistance value.

[0094] Figure 8 This is a graph showing the repeatability test results of the gas sensor prepared in this embodiment for 100ppmNO2 at room temperature. It can be seen from the figure that after the sensitive membrane formed by the three-dimensional Ni-Al LDHs nanoflower composite material prepared by g-C3N4 doping adsorbs NO2, the resistance value decreases rapidly. After 7 consecutive cycles of adsorption-desorption of 100ppm NO2, the repeatability is good.

[0095] Fig. 9 This is the dynamic response curve of the gas sensor prepared in Example 8 to 100 ppm NO2 at different relative humidity (RH) at room temperature. The results show that the gas sensor has good moisture resistance under different humidity conditions ranging from 25% to 60%.

Claims

1. A method for preparing a three-dimensional Ni-Al LDHs nanoflower composite material, characterized in that: First, urea is calcined twice to obtain a two-dimensional g-C3N4 precursor, and then the two-dimensional g-C3N4 precursor, nickel nitrate hexahydrate, aluminum nitrate nonahydrate, ammonium fluoride and urea are placed in deionized water, and stirred to obtain a mixed solution I. The mixed solution I is placed in an autoclave for heating treatment, and after cooling, a mixed solution II is obtained. The mixed solution II is filtered to collect the precipitate, and after washing and drying, a three-dimensional Ni-Al LDHs nanoflower composite material is obtained.

2. The method for preparing a three-dimensional Ni-Al LDHs nanoflower composite material according to claim 1, characterized in that: The heating rate of the first calcination of urea is 2.4°C / min, the first calcination temperature is 500-550°C, and the calcination time is 2-4h; the heating rate of the second calcination of urea is 5°C / min, the second calcination temperature is 20-50°C lower than the first calcination temperature, and the calcination time is 2h.

3. A method for preparing a three-dimensional Ni-Al LDHs nanoflower composite material according to claim 1 or 2, characterized in that: The mass to volume ratio of the two-dimensional g-C3N4 precursor, nickel nitrate hexahydrate, aluminum nitrate nonahydrate, ammonium fluoride, urea and deionized water is 0.12-0.15g: 0.1g: 0.05g: 0.04-0.06g: 0.1g: 70-80mL; the stirring time is 30-60min.

4. The method for preparing a three-dimensional Ni-Al LDHs nanoflower composite material according to claim 3, characterized in that: The mixed solution I is heated at 100-150° C. for 18-24 hours.

5. The method for preparing a three-dimensional Ni-Al LDHs nanoflower composite material according to claim 4, characterized in that: The washing is to wash the precipitate obtained by filtration with deionized water and anhydrous ethanol in sequence, and the drying is to dry at 60 to 90° C. for 12 to 24 hours.

6. A three-dimensional Ni-Al LDHs nanoflower composite material prepared by the method for preparing a three-dimensional Ni-Al LDHs nanoflower composite material according to any one of claims 1 to 5, characterized in that: The composite material is a g-C3N4 doped Ni-Al LDHs composite material. The microscopic morphology of the composite material is a nano-scale three-dimensional flower-like structure composed of a plurality of lamellae. The diameter of the overall three-dimensional flower-like structure is 2 to 3 μm, and the specific surface area is 140 to 150 m 2 / g.

7. An application of the three-dimensional Ni-Al LDHs nanoflower composite material as claimed in claim 6 in NO2 gas detection.

8. The use of the three-dimensional Ni-Al LDHs nanoflower composite material in NO2 gas detection according to claim 7, characterized in that: The application is to prepare a gas sensor using a three-dimensional Ni-Al LDHs nanoflower composite material.

9. The use of the three-dimensional Ni-Al LDHs nanoflower composite material in NO2 gas detection according to claim 8, characterized in that: The preparation method of the gas sensor is to ultrasonically disperse the Ni-Al LDHs nanoflower composite material described in claim 6 in 1 to 10 times the volume of an ethanol solution to obtain a uniformly dispersed suspension, then coat the suspension on an Au interdigital electrode cleaned with ethanol, and dry it at 50 to 90° C. for 2 to 5 hours to obtain the gas sensor.

10. The use of the three-dimensional Ni-Al LDHs nanoflower composite material in NO2 gas detection according to claim 9, characterized in that: The application is to place the gas sensor prepared from the three-dimensional Ni-Al LDHs nanoflower composite material according to claim 6 under conditions of 15 to 35° C. and 20 to 80% humidity to detect the NO2 gas concentration in the gas to be tested.

Citation Information

Patent Citations

  • Preparation method of sea urchin-shaped g-C3N4 / NiAl-LDH semiconductor heterojunction

    CN110665527A